Working with Arts in Nurse Education - Julie Borup Jensen (Stockholm University Press, 2011)
This article outlines ideas and some results of a design-for-learning experiment, involving nurse students working with arts in the nurse education in Denmark. The original purpose of the experiment was to investigate new ways of supporting personal knowledge building and building of professional judgement skills for nurse students, according to a phenomenological and aesthetic approach to learning. However, the results and learning outcome for the students surprisingly showed that working with arts had the effect that the nurse students began acting creatively in their building of personal and professional knowledge. The experiment suggests that working with arts can contribute to building nurse students' building of 'relational creativity' as a basis for professional judgement. Relational creativity is not an established theoretical concept, but the article argues that the term might have significance not only to nurse students, but also to new ways of thinking about knowledge, professional judgement and learning perspectives in relational professions in general.